P‐156: One Step Stabilized Azo Dye Photoalignment for Mass Production. Issue 1 (May 2017) - Meng, Cuiling; Tseng, Man-Chun; Srivastava, Abhishek K.; Chigrinov, V. G.; Kwok, Hoi-Sing
Abstract : A novel azo dye stabilization method was presented that only requires single‐shot UV light exposure. The proposed photoalignment layer offers highly acceptable thermal and photo‐stability, as well as low pre‐tilt angle (0.2°) and low image sticking (1.01). Also, high VHR (99%) and low RDC (<10mV) comparable to that of PI rubbing have been achieved. Furthermore, the ability of multi‐domain alignment has been demonstrated that shows a great potential in a wide range of electro‐optical devices.